5
$\begingroup$

How to prove

$$\sum_{n=1}^\infty\frac{H_{n}^2}{(2n+1)^3}=\frac{31}{8}\zeta(5)-\frac{45}{8}\ln2\zeta(4)+\frac72\ln^22\zeta(3)-\frac78\zeta(2)\zeta(3)$$

where $H_n$ is the harmonic number and $\zeta$ is the Riemann zeta function.


Here is my approach and would like to see different methods if possible.

Using the identity

$$\frac{\ln^2(1-x)}{1-x}=\sum_{n=1}^\infty (H_n^2-H_n^{(2)})x^n$$

replace $x$ with $x^2$, then multiply both sides by $\frac12\ln^2x$ and integrate from $x=0$ to $1$ we get

$$\sum_{n=1}^\infty\frac{H_n^2-H_n^{(2)}}{(2n+1)^3}=\frac12\int_0^1\frac{\ln^2x\ln^2(1-x^2)}{1-x^2}\ dx\\=\frac1{16}\int_0^1\frac{\ln^2x\ln^2(1-x)}{\sqrt{x}(1-x)}\ dx=\frac1{16}\left.\frac{\partial^4}{\partial a^2\partial b^2}\text{B}(a,b)\right|_{a\mapsto 1/2\\b\mapsto0^{+}}$$

with help of Mathematica we have

$$\left.\frac{\partial^4}{\partial a^2\partial b^2}\text{B}(a,b)\right|_{a\mapsto 1/2\\b\mapsto0^{+}}=248\zeta(5)-90\ln2\zeta(4)+56\ln^22\zeta(3)-112\zeta(2)\zeta(3)$$

Also, from here we have

$$\sum_{n=1}^\infty\frac{H_{n}^{(2)}}{(2n+1)^3}=\frac{49}{8}\zeta(2)\zeta(3)-\frac{93}{8}\zeta(5)$$

Combining these two result, we get the desired answer.


Note: You can find here details about the derivative of beta function.

$\endgroup$
4
$\begingroup$

Assuming that we know the value of ${\displaystyle \sum_{n\geq1}\frac{H_{n}^{\left(2\right)}}{\left(2n+1\right)^{3}}}$, we can use a classic result of Flajolet and Salvy:

Theorem. Assume that $r\left(s\right)$ is a rational function such that:

a) $r\left(s\right)=O\left(s^{-2}\right)$ at infinity,

b) $r\left(s\right)$ has no pole in $\mathbb{Z}\setminus\left\{ 0\right\}$.

Then $$2\sum_{n\geq1}r\left(n\right)H_{n}+\sum_{n\geq1}r^{\prime}\left(n\right)=-\sum_{\beta\in S}\underset{s=\beta}{\mathrm{Res}}\left(r\left(s\right)\left(\psi\left(-s\right)+\gamma\right)^{2}\right)$$ and $$3\sum_{n\geq1}r\left(n\right)H_{n}^{2}-3\sum_{n\geq1}r\left(n\right)H_{n}^{\left(2\right)}+3\sum_{n\geq1}r^{\prime}\left(n\right)H_{n}+\sum_{n\geq1}\left(\frac{r^{\prime\prime}\left(n\right)}{2}-3r\left(n\right)\zeta\left(2\right)\right)$$ $$=-\sum_{\beta\in S}\underset{s=\beta}{\mathrm{Res}}\left(r\left(s\right)\left(\psi\left(-s\right)+\gamma\right)^{3}\right)$$where $\psi\left(s\right)$ is the Digamma function and $S$ is the set of the poles of $r\left(s\right)$.

Then, tacking $r\left(s\right)=\left(2s+1\right)^{-3}$, we have $$3\sum_{n\geq1}\frac{H_{n}^{2}}{\left(2n+1\right)^{3}}-3\sum_{n\geq1}\frac{H_{n}^{\left(2\right)}}{\left(2n+1\right)^{3}}-18\sum_{n\geq1}\frac{H_{n}}{\left(2n+1\right)^{4}}$$ $$+\sum_{n\geq1}\left(\frac{24}{\left(2n+1\right)^{5}}-\frac{3\zeta\left(2\right)}{\left(2n+1\right)^{3}}\right)=-\underset{s=-1/2}{\mathrm{Res}}\left(\frac{\left(\psi\left(-s\right)+\gamma\right)^{3}}{\left(2s+1\right)^{3}}\right)$$ and, with $r(s)=(2s+1)^{-4},$ $$2\sum_{n\geq1}\frac{H_{n}}{\left(2n+1\right)^{4}}-8\sum_{n\geq1}\frac{1}{\left(2n+1\right)^{5}}=-\underset{s=-1/2}{\mathrm{Res}}\left(\frac{\left(\psi\left(-s\right)+\gamma\right)^{2}}{\left(2s+1\right)^{4}}\right).$$ Combining these results, we get the thesis.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Nice work Marco... (+1) $\endgroup$ – Ali Shather Oct 12 '19 at 14:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.